2010
DOI: 10.1007/s12237-010-9312-3
|View full text |Cite
|
Sign up to set email alerts
|

Non-linear Responses of a Coastal Aquatic Ecosystem to Large Decreases in Nutrient and Organic Loadings

Abstract: Between 1991 and 2000, Boston Harbor, a bayestuary in the northeast USA, experienced a decrease in loadings of total nitrogen (TN), total phosphorus (TP), and particulate organic carbon (PC) of between ∼80% and ∼90%. The average concentrations of TN and TP in the harbor water column were decreased in linear proportion to the loadings. The changes to the chlorophyll-a (chl-a), PC, and bottom water DO concentrations were curvilinear relative to the loadings, with larger changes at low than high loadings. For TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…To describe site differences, and to facilitate cross-reference to other studies Taylor, 2010;Taylor et al, 2011), data for each site were averaged according to time periods corresponding to treatment changes (Fig. 2), These periods roughly match those previously defined by Taylor (2010) (Table 1), but exclude Period I because we have limited data from that period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To describe site differences, and to facilitate cross-reference to other studies Taylor, 2010;Taylor et al, 2011), data for each site were averaged according to time periods corresponding to treatment changes (Fig. 2), These periods roughly match those previously defined by Taylor (2010) (Table 1), but exclude Period I because we have limited data from that period.…”
Section: Discussionmentioning
confidence: 99%
“…There is a great deal of interest in evaluating how successful these attempts have been and in learning how to predict the trajectory of eutrophication reversal or "oligotrophication" (Duarte, 2009;Nixon, 2009). Studies to date Taylor et al, 2011) have shown that not all estuaries respond similarly to decreases in nutrient loading, and that some systems do not revert to their original conditions. Sediments play an important role in organic matter decomposition and nutrient cycling (Nixon, 1981;Boynton and Kemp, 1985) and may impact the rate at which estuaries respond to changes in nutrient loading.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, while the eutrophication process leading to ecosystem degradation is well studied and understood, our knowledge on coastal ecosystem recovery following significant nutrient reductions is limited and suffers from scarcity of longterm large-scale ecosystem studies. Existing studies indicate that complete recovery of coastal ecosystems to a previous baseline is rarely a realistic assumption (Lotze et al 2011;Duarte et al 2015) because degradation and recovery typically follow different non-linear pressure-response pathways and the interaction of multiple pressures may lead to shifts in baseline conditions (Duarte et al 2009;Carstensen et al 2011;Taylor et al 2011). …”
Section: Introductionmentioning
confidence: 99%
“…Anthropogenic manipulation of freshwater inflow alters salinity distributions that affect estuarine organisms and the structure of food webs (Livingston et al, 1997;Powell et al, 2003;Tolley et al, 2005;Gillson, 2011;Petes et al, 2012). Nutrient loading is a function of freshwater discharge and the incoming concentrations of N and P (Boynton et al, 2008;Greening et al, 2011;Taylor et al, 2011). Symptoms of estuarine eutrophication are often ascribed to the increased loading of dissolved nutrients (e.g.…”
Section: Introductionmentioning
confidence: 99%